FAKTOR PREDIKTOR GANGGUAN PENGLIHATAN BERAT DAN KEBUTAAN PADA PENDERITA DIABETES DI DAERAH ISTIMEWA YOGYAKARTA - Rimawati Aulia Insani Sadarang; Hari Kusnanto; Mohammad Bayu Sasongko (Berita Kedokteran Masyarakat (BKM), 2017)
Predictors of severe visual impairment and blindness among diabetic patients in Special Territory of YogyakartaPurposeThe purpose of this study was to identify any predictors of severe visual impairment and blindness among diabetic patients in Daerah Istimewa Yogyakarta.MethodsThis research was a cross-sectional study by analyzing registry data from (JOGED.COM). Data included sociodemographic characteristics, diabetic status, health record, and eye diseases. The analysis was done using chi-square and simple logistic regression tests follow with semi-partial correlation, stratification tests and multilevel analysis with Generalized Estimation Equation (GEE).ResultsAs much as 1093 data were included in this study. The prevalence of severe visual impairment was 12% and blindness was 6.5%. Cataract, diabetic retinopathy and diabetes duration >10 years were statistically significant with severe visual impairment and blindness while glaucoma and hypertension only significant with severe visual impairment. The contribution of cataract in severe visual impairment (4.73%) and blindness (3.11%) was highest among eye diseases. There was modification effect of cataract to severe visual impairment and blindness by diabetes duration. Based on GEE, cataract, diabetic retinopathy and diabetes duration > 10 years was the best model to predict the occurrence of severe visual impairment and blindness.ConclusionsPredictors of severe visual impairment and blindness among diabetic patients in Daerah Istimewa Yogyakarta were the cataract, diabetic retinopathy and diabetes duration >10 years. Modification effect of cataract by diabetes duration only was significant in a model to predict blindness.